A regra é clara, o direito não: entre a subordinação fática e a ausência de profissionalização dos árbitros de futebol no Brasil. - Andrade, Ályka Kalinny Costa De (2025)
The present study critically analyzes the absence of an employment relationship and the precarious nature of football referees' work in Brazil, in light of current legislation and institutional practices. Starting from the sociocultural and economic relevance of football, the research highlights the essential role of referees as guarantors of order and impartiality in competitions. Through a qualitative approach and documentary analysis, the study contrasts the legal classification of referees as self-employed with the factual reality, which reveals features such as integration into the organizational structure, continuity of service provision, economic dependence, and subjection to directives — all of which are incompatible with true professional autonomy. The national legal framework is examined, including the General Sports Law (Law no 14.597/2023), the former Pelé Law, and the repealed Law no 12.867/2013, pointing out legal contradictions and omissions. The research also draws on international experiences, such as the English PGMOL model, to demonstrate the feasibility of full and independent professionalization of refereeing. Based on the principle of the primacy of reality, the study concludes that maintaining the current legal classification undermines referees’ professional dignity, their functional independence, and the quality of competitions, making the specific regulation of the category urgent, as proposed by Bill no 864/2019.